2019
DOI: 10.1155/2019/6321427
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ANGPTL8 Is Associated with the Presence of Metabolic Syndrome and Insulin Resistance in Polycystic Ovary Syndrome Young Women

Abstract: Background. ANGPTL8 has been reported to be a regulator of lipid metabolism, and it is associated with insulin resistance (IR) and metabolic syndrome (MetS). We investigated whether ANGPTL8 plays a role in MetS. Methods. ANGPTL8 and adiponectin concentrations were measured in PCOS patients with or without MetS and in their corresponding healthy controls. The association of circulating ANGPTL8 with adiponectin and other parameters was also examined. Results. Circulating ANGPTL8 concentrations were higher in PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
(54 reference statements)
3
10
0
Order By: Relevance
“…In the correlation analysis performed betatrophin levels showed positive correlations with BMI, FPG, insulin, HOMA-IR, TC, TAG, LDL-C, LH and TT in obese and non-obese PCOS patients. This finding was consistent with the Pu et al [8], Luo et al [10], Qu et al [15], Sahin et al [1] and Duan et al [12]. A strongly positive correlation was found between circulating betatrophin levels and LH, free-testosterone, HOMA-IR, BMI, insulin, FBG, and lipid profile (triglycerides, LDL-C, and total cholesterol) in both groups Calan et al [16].…”
Section: Fig 4 Correlation Between Betatrophin and Wisp1 Non-obese supporting
confidence: 90%
See 2 more Smart Citations
“…In the correlation analysis performed betatrophin levels showed positive correlations with BMI, FPG, insulin, HOMA-IR, TC, TAG, LDL-C, LH and TT in obese and non-obese PCOS patients. This finding was consistent with the Pu et al [8], Luo et al [10], Qu et al [15], Sahin et al [1] and Duan et al [12]. A strongly positive correlation was found between circulating betatrophin levels and LH, free-testosterone, HOMA-IR, BMI, insulin, FBG, and lipid profile (triglycerides, LDL-C, and total cholesterol) in both groups Calan et al [16].…”
Section: Fig 4 Correlation Between Betatrophin and Wisp1 Non-obese supporting
confidence: 90%
“…The mechanism underlying the association between betatrophin and LH may be related to the signaling pathways between pituitary and liver, which may result in the stimulation of betatrophin by LH as a pituitary hormone. Conversely Wang et al [13] and Pu et al [8] founded that there were significant negative correlation between betatrophin level and insulin, HOMA-IR and BMI. These contradicting results may be due to differences in methodology, study design, participants, and sample sizes Varikasuvu et al [11].…”
Section: Fig 4 Correlation Between Betatrophin and Wisp1 Non-obese mentioning
confidence: 95%
See 1 more Smart Citation
“…Irisin is a myokine and expressed in muscle as the type I membrane precursor protein FNDC5, which is proteolytically cleaved, secreted into the circulatory system, and found to improve muscle IR [17]. These cytokines are also believed to be involved in metabolic diseases, such as T2DM, PCOS, and MetS [13,[18][19]. However, a single cytokine can not reflect the whole pathological process, but only one aspect of disease development.…”
Section: Introductionmentioning
confidence: 99%
“…ANGPTL8 levels were increased in diabetes [ 14 – 16 ], dyslipidaemia [ 17 , 18 ], CVD [ 19 ], renal function [ 20 – 22 ], obesity [ 23 ], hypertension [ 24 ], and nonalcoholic fatty liver [ 25 ]. Furthermore, studies have revealed that ANGPTL8 levels also increased with age [ 26 , 27 ], suggesting its potential association with aging and with age-related metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%